Análise geoambiental da bacia hidrográfica do rio Mucambinho-Ce - Evangelista, Francisca Sinhá Moreira (2009)
The objective of this work is to carry out an integrated study about environmental conditions and dynamics, the nature potentially and the supportiveness capacity of this ecosystem, proposing later, a collection of sustainable environmental measures. The Rio Mucambinho water basin is inserted in four cities of Ceara’s North region, such as Meruoca, Alcântaras, Sobral and Coreaú. The basin occupy an area of 100km², its sources located in Meruoca district, specifically in Meruoca’s Moutain and to flow into the Acaraú river, located in Sobral city. The methodology was developed in three stages: theoretical foundation, field surveys and office activities. In this study, the basin was characterized though of analysis of the geoenvironmental systems attributes (geology, geomorphology, climate, water resources, soils, vegetation and animal’s species), socioeconomics aspects and the forms of the land occupations and uses. It was made still the hidroclimatical analysis with a Mucambinho river division. Later this separation it was identified the environmentals systems of the basin according to the geosystemic methodology proposal by Bertrand (1969), whose units has been represents on the mapping of environmental systems with scale 1.90.000. In addiction, it was classified the systems in: stable, unstable or intergrades according to ecodynamic of Tricart (1977). This integrated approach allowed that in the nature resources diagnosis, environmental quality assessment, it was considered the attributes collection, including so, the interpretation of humans, biologics and physics aspects. Therefore, it was possible to elaborate proposals for planning of the use and handling of the nature resources, and to define the main socioenvironmental impacts: deforestation, bonfires, changes of water resources, erosive processes, loss vegetation and animals, lost fertility of soils, among others. Finally, with this integrated analysis presented some sustainable environmental measures than can contributes for minimize the impacts and to improve the preservation of environmental quality of the Mucambinho water basin